A Coenzima Q10 atenua o comportamento tipo-depressivo induzido por encefalopatia séptica e regula danos oxidativos e inflamatórios - Souza, Flávia Reis Ferreira De (2022)
Patients who survive sepsis have brain injuries, which induce the development of long-term depressive symptoms, impairing their longevity. Coenzyme Q10 (CoQ10) has nutritional properties, antioxidant, anti-inflammatory and neuroprotective actions. In front of that, the effect of CoQ10 on depression type symptoms in adult male Wistar rats surviving sepsis induced by cecal ligation and perforation (CLP) was evaluated. Initially, we evaluated the depressive type behavior on the 7th, 14th and 21st day after the simulation (control group – Sham) or sepsis induction, by open field behavioral tests, forced swimming and sucrose preference. This temporal evaluation aimed to define the most convenient period to carry out the treatment with CoQ10. The CLP group showed depressive-like behavior on the 7th and 14th day, characterized by reduced swimming and climbing time, increased immobility time, accompanied by a reduction in sucrose preference when compared to the control group. Then, another group of animals received the following treatment: vehicle (2 ml/kg) or CoQ10 (100 or 300 mg/kg, p.o), for 7 consecutive days, between the 7th and 14th day after the surgery. On the 14th day, the animals were submitted to the aforementioned behavioral tests and were posteriorly sacrificed for dissection of the hippocampus, hypothalamus and prefrontal cortex, to evaluate oxidative damage by NADPH oxidase, TBARS, TRAP, GSH and GSSH, expression of inflammatory mediators (TNF-α, iNOS, COX-2 and NRF2). Behavioral data suggest that CoQ10 improvement depressive-like behavior in rodents, attenuating anhedonia in the sucrose preference test, manifesting an increase between swimming and climbing times, in addition to a reduction in immobility time in the CLP groups treated with 100 and 300 mg/kg of CoQ10 compared to the CLP + vehicle group. About the tests that evaluated the parameters of oxidative stress, a significant increase was found in the expressions of NADPH oxidase and MDA among the CLP vehicle animals compared to the control group, which were attenuated after treatment with CoQ10.